Assessing the Variations in Breast/Ovarian Cancer Risk for Chinese BRCA1/2 Carriers. (26th March 2022) - Li, Ang; Hao, Shuai; Luo, Jiaqi; Zi, Yi; Lan, Zhaoji; Zhou, Tianliangwen; Zhi, Qihuan; Zhan, Jiamin; Sun, Gang; Shi, Yujian; Luo, Donglin
Abstract : Background . Cancer risks vary in different BRCA1/2 mutations. We are interested in identifying regions associated with elevated/reduced risks of breast/ovarian cancers in the Chinese population and comparing with previously reported Caucasian-based breast/ovarian cancer cluster regions (OCCR/BCCR). We also aim to characterize the distribution and estimate the cancer risks of different Chinese recurrent mutations. Methods . A total of 3, 641 cancer-free women and 4, 278 female cancer patients were included in the study. Germline BRCA1/2 status was detected with amplicon-based next-generation sequencing. We calculated the odds ratio (OR) of breast cancer and OR of ovarian cancer, and their ratio of the two ORs (ROR) for each region. ROR >1 indicated elevated odds of breast cancer and/or decreasing odds of ovarian cancer, and vice versa. The frequency, distribution, and penetrance of six known Chinese founder mutations were characterized, respectively. Haplotype analysis and age estimation were performed on the most prevalent founder mutation BRCA1 : c.5470_5477del. Results . A total of 729 subjects were detected with germline BRCA1/2 deleterious mutations. The putative Chinese OCCR/BCCR partially overlapped with Caucasian-based OCCR/BCCR and shared structural-functional characteristics. The six known Chinese founder mutations greatly vary in both distribution and penetrance. The two widely spread mutations are estimated to convey low penetrance, while the area-restricted founder mutations seemed to confer higher/complete penetrance. BRCA1 : c.5470_5477del is estimated to have emerged ∼2, 090 years ago (70 B.C.) during the Han dynasty. Conclusions . BRCA1/2 carriers with different genotypes have significantly different cancer risks. An optimal risk assessment should be mutation specific, rather than concerning a single figure.